[tex]xy'+y=-5xy^2[/tex]
Divide through the ODE by the largest power of [tex]y[/tex], assuming [tex]y\neq0[/tex]:
[tex]xy^{-2}y'+y^{-1}=-5x[/tex]
By the chain rule, [tex](y^{-1})'=-y^{-2}y'[/tex]. So substitute [tex]z=y^{-1}[/tex] and [tex]-z'=y^{-2}y'[/tex] to get
[tex]-xz'+z=-5x[/tex]
which is linear in [tex]z[/tex]. Multiply both sides by [tex]-\frac1{x^2}[/tex]:
[tex]\dfrac{z'}x-\dfrac z{x^2}=\dfrac5x[/tex]
Now the left side is the derivative of a product, so we can condense this as
[tex]\left(\dfrac zx\right)'=\dfrac5x[/tex]
Integrate both sides with respect to [tex]x[/tex]:
[tex]\dfrac zx=5\ln|x|+C[/tex]
[tex]z=5x\ln|x|+Cx[/tex]
Solve for [tex]y[/tex]:
[tex]\dfrac1y=5x\ln|x|+Cx\implies\boxed{y=\dfrac1{5x\ln|x|+Cx}}[/tex]